SIMPONIS: A Web-Based Student Violation Point Information System for Enhanced Efficiency and Transparency with an Early Warning Feature - Rahma Livamianti; Hadi Kurnia Saputra; Elfi Tasrif; Lativa Mursyida (Sagamedia Teknologi Nusantara, 2024)
The Web-Based Student Violation Point Information System (SIMPONIS) was developed to enhance the efficiency and transparency of recording and monitoring student violations at SMA Negeri 1 Ranah Pesisir. This system is designed to replace the previous manual method, which was prone to errors, data duplication, and delays in handling violations. Through SIMPONIS, guidance counselors can record and monitor student violation points in real-time and provide accurate reports to students and parents. The system integrates an Early Warning Feature that alerts users when a student’s violation points reach a critical threshold, allowing for corrective actions to be taken promptly. The system was tested using the black box method, ensuring that all functions operate as expected. The test results show that SIMPONIS provides an effective solution for managing student violation data, increases parent involvement in monitoring their children, and simplifies the administrative tasks of guidance counselors. Therefore, this system has the potential to be implemented more broadly in other educational institutions.